2017
DOI: 10.1155/2017/5034827
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Evaluation of Pharmacological Potentials of Secondary Bioactive Metabolites of Dalbergia candenatensis Leaves

Abstract: Background. Dalbergia species has wide range of secondary metabolites and is traditionally used in treatment of painful micturition, swelling, and leprosy and as blood tonic. The study evaluates membrane stabilizing, anticoagulant, analgesic, cytotoxic, subacute anti-inflammatory, and depression potentials of D. candenatensis leaves metabolites. Methods. Membrane stabilizing activity was evaluated by hypotonic induced hemolysis assay, whereas anticoagulant activity is done through extrinsic pathway by measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…This experiment was carried out as described by Anisuzzman et al (2017) [9]. The open field device consisted of a smooth field of half square meter with a series of squares.…”
Section: Open Field Testmentioning
confidence: 99%
“…This experiment was carried out as described by Anisuzzman et al (2017) [9]. The open field device consisted of a smooth field of half square meter with a series of squares.…”
Section: Open Field Testmentioning
confidence: 99%
“…It is widely used bench-top method because of the simple laboratory setup and small amount of sample is required [60]. The mechanism involved in the cytotoxicity of the brine shrimp can be of pharmacological effects linked to enzyme inhibition, ion channel interference or cytotoxicity [12,61]. In the present study the extract showed potential cytotoxic activity (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…The extract was subjected to acetic induced writhing test in mice according to the method described by Anisuzzman M [12]. Experimental mice were randomly screened and separated into four groups with six mice in each.…”
Section: Evaluation Of Analgesic Activity Writhing Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The hole board test was conducted following the methods of Anisuzzman et al 2017 [10]. Mice were divided into 6 groups and each group comprised of 5 mice with 20-30 g in weight.…”
Section: Hole Board Test Of Crude Extractmentioning
confidence: 99%